A study on the impact of facilities management on students’ academic achievement among university students / Anom Munajat Zurainan - Zurainan, Anom Munajat (2020)
Facilities management is one of the important aspects that need to be considered in every educational institution. Literatures shows that a good management of the facilities in an educational institution can affect students’ learning process and subsequently impact the students’ academic achievement. Thus, the educational institution must critically understand how to manage the facilities well. The purpose of this research is to investigate the different facilities management and how it impacts students’ academic achievement. This research was carried out in Universiti Teknologi MARA Cawangan Perlis with the main objective to investigate the management of facilities such as e-learning facility, classroom, library, and hostels apart from that, it also aims to determine the relationship between all of these facilities’ management, whether they have any effect on the students’ academic achievement. Data was collected using questionnaire which were distributed to 217students. Data was then analyzed using SPSS software and a few analysis were carried out such as descriptive analysis, correlations and regression analysis. The results shown that three factors which is e-learning, library, and hostel have significant impact on students’ academic achievement while classroom have no significant impact on students’ academic achievement. The results of this study could be used by educational institution to better plan and manage their facilities and subsequently help students to increase their academic achievement.